2008
DOI: 10.1093/cercor/bhn126
|View full text |Cite
|
Sign up to set email alerts
|

Selective Attention to Semantic and Syntactic Features Modulates Sentence Processing Networks in Anterior Temporal Cortex

Abstract: Numerous studies have identified an anterior temporal lobe (ATL) region that responds preferentially to sentence-level stimuli. It is unclear, however, whether this activity reflects a response to syntactic computations or some form of semantic integration. This distinction is difficult to investigate with the stimulus manipulations and anomaly detection paradigms traditionally implemented. The present functional magnetic resonance imaging study addresses this question via a selective attention paradigm. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
149
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(174 citation statements)
references
References 45 publications
(60 reference statements)
22
149
2
1
Order By: Relevance
“…There has also been evidence implicating the left ATL in syntactic processing (Brennan et al, 2010;Dronkers et al, 2004;Friederici et al, 2000aFriederici et al, , 2000bHumphries et al, 2005Humphries et al, , 2006Mazoyer et al, 1993;Noppeney and Price, 2004;Rogalsky and Hickok, 2009;Vandenberghe et al, 2002). For example, Brennan et al (2010) investigated the effects of syntactic node count for each word of Alice in Wonder Land in a passive listening study and observed left ATL but not left IFG activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been evidence implicating the left ATL in syntactic processing (Brennan et al, 2010;Dronkers et al, 2004;Friederici et al, 2000aFriederici et al, , 2000bHumphries et al, 2005Humphries et al, , 2006Mazoyer et al, 1993;Noppeney and Price, 2004;Rogalsky and Hickok, 2009;Vandenberghe et al, 2002). For example, Brennan et al (2010) investigated the effects of syntactic node count for each word of Alice in Wonder Land in a passive listening study and observed left ATL but not left IFG activation.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, Broca's area or left inferior frontal gyrus (IFG) has been most associated with syntax (Ben-Shachar et al, 2003;Ben-Shachar et al, 2004;Bornkessel-Schlesewsky et al, 2009;Caplan et al, 2008;Caplan et al, 2000;Carramazza and Zurif, 1976;Dapretto and Bookheimer, 1999;Embick et al, 2000;Friederici et al, 2006;Grodzinsky, 2001;Just et al, 1996;Santi and Grodzinsky, 2007;Stromswold et al, 1996). In addition, the left anterior temporal lobe (ATL) has often been linked to computations related to the manipulation of syntactic structure (Brennan et al, 2010;Dronkers et al, 2004;Friederici et al, 2000a;Friederici et al, 2000b;Humphries et al, 2005;Humphries et al, 2006;Mazoyer et al, 1993;Noppeney and Price, 2004;Rogalsky and Hickok, 2009;Tyler et al, 2011;Vandenberghe et al, 2002). Finally, several studies suggest a potential role for left posterior superior temporal sulcus and gyrus (STS/STG) in syntactic processing (Constable et al, 2004;Cooke et al, 2002;Hasson et al, 2006;Tyler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, although much evidence implicates the LATL in syntactic combinatorial processing, a number of researchers have also suggested that this region plays an important role in semantic combinatorial operations as well. For example, when participants are asked to monitor sentences for semantic anomalies, a subset of the LATL shows increased activity compared with monitoring for syntactic violations (Rogalsky and Hickok, 2009). Also, scrambling the content words of sentences modulates activity in the LATL, although the direction of this effect has varied, with scrambled sentences eliciting both more (Vandenberghe et al, 2002) and less (Humphries et al, 2006) LATL activity compared with normal sentences.…”
Section: Atl and Vmpfc Effects Of Compositionmentioning
confidence: 99%
“…These regions may process domain-specific semantic features (that were not reproduced in our control conditions) including phonological or complex acoustic features of voice or speech on the one hand (e.g., ref. 34) and complex visual attributes of manual or facial stimuli on the other (e.g., ref. 35).…”
Section: Shared Activations For Perception Of Symbolic Gesture and Spmentioning
confidence: 99%